2021
DOI: 10.1024/2673-8627/a000015
|View full text |Cite
|
Sign up to set email alerts
|

Overall Job Performance, Remote Work Engagement, Living With Children, and Remote Work Productivity During the COVID-19 Pandemic

Abstract: Abstract. The COVID-19 pandemic caused a significant and rapid shift from work in presence to remote work (RW). This rapid change represented a challenge for employees, who had to deal with new work procedures in houses often crowded with their children. This study investigated whether the engagement toward this work arrangement mediates the relationship between perceived overall job performance and employees’ remote work productivity. Furthermore, it tested whether the relationships between perceived overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…In particular, one-third of the people who teleworked, and one-fifth of those who worked face-to-face, signaled a situation of workload. Thus, it is likely that teleworkers did not work under the appropriate conditions, and that this sudden adaptation to teleworking implied a greater workload for them [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, one-third of the people who teleworked, and one-fifth of those who worked face-to-face, signaled a situation of workload. Thus, it is likely that teleworkers did not work under the appropriate conditions, and that this sudden adaptation to teleworking implied a greater workload for them [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the confinement, although some studies (e.g., [ 11 , 39 ]) have shown the benefits of working from home reconciling work with family life, most of them have highlighted the difficulties generated by this. In terms of benefits, Toscano and Zappalà’s [ 40 ] study showed that living with children during confinement positively moderated the relationship between overall performance and remote work productivity. Having to respond to children’s needs would probably make people more likely to work in a more motivating way.…”
Section: Conceptualization Of Stress and Its Predictorsmentioning
confidence: 99%
“…This finding is in line with the self-expansion approach ( Mattingly and Lewandowski, 2013 ), which indicates that new activities (in this case, telecommuting) support the development of people’s resources through their engagement with the new activities. This theory can explain an intraindividual expansion driven by an external condition, such as working from home ( Toscano and Zappalà, 2021 ). Although not initially postulated by this study, according to this theory, the moderating effect of family interfering with work on the relationship between the extent of telecommuting and psychological detachment from work can be explained by the energizing effect and mutual exchange of resources that occur between close people, leading to self-expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Although not initially postulated by this study, according to this theory, the moderating effect of family interfering with work on the relationship between the extent of telecommuting and psychological detachment from work can be explained by the energizing effect and mutual exchange of resources that occur between close people, leading to self-expansion. In the case of employees who work from home, interference from family, such as attending to the needs of their children, and engaging in arguments with their spouse, may motivate the employees to seek self-expansion and become considerably active to fulfill both work and family roles ( Toscano and Zappalà, 2021 ). This self-expansion may lead employees to increased fulfillment in their work and result even in enhanced psychological detachment from work during non-work time.…”
Section: Discussionmentioning
confidence: 99%
“…Many employees rediscovered their ability to innovate and improvise when they confronted boredom and isolation head-on. The lack of social interaction in the workplace was replaced by a wider imagination of how technology could be deployed to create a sense of collaboration (Toscano and Zappala, 2021). "I didn't allow myself to work in a vacuum.…”
Section: Work Meaningfulnessmentioning
confidence: 99%